Photoluminescence enhancement in thin films of PbSe nanocrystals - Christova, Christina G.; Stouwdam, J. W.; Eijkemans, T. J.; Silov, A. Yu.; van der Heijden, R. W.; Kemerink, Martijn; Janssen, René A. J.; Salemink, Huub W. (Applied physics letters, 2008)
Remarkable photoluminescence enhancement (PLE) in submonolayer films of PbSe nanocrystals (NCs) upon continuous illumination was observed. The intensity increase from films on InP substrates was highest in vacuum, while for films on Si/SiO2Si/SiO2<mtext>Si</mtext>/<mtext>SiO</mtext>2 substrates the PLE was stronger in air. The magnitude of the PLE was found to depend on the excitation intensity, being higher for a weaker irradiation power. The possible mechanisms behind the phenomenon of the PLE are discussed and it is suggested to originate mainly from charge trapping outside the NCs core.
Gesehen am 11.12.2019